Flouted Maxims in Red Dead Redemption 2: A Case Study of Arthur Morgan in the Mission A Fine Night of Debauchery - Muhammad Ilman Fikri (Fakultas Ilmu Budaya, 2025)
This thesis analyzes how Arthur Morgan, the main character in Red Dead Redemption 2, strategically flouts Grice’s conversational maxims during the mission A Fine Night of Debauchery. The study focuses on identifying which maxims were flouted and how these flouted maxims function as an indirect communication strategy that helps Arthur conceal his true identity while undercover. A qualitative descriptive approach was used to examine 10 utterances from the mission through the lens of Grice's theory of conversational maxims. The findings show that Arthur has flouted 3 out of 4 conversational maxims: quality, quantity, and relation, with the maxim of quality being the most frequently flouted, indicating that his statements often lack truth or evidence. He also tends to provide either more or less information than necessary, which means he flouted the maxim of quantity. Furthermore, his responses often lack relevance to the ongoing topic, which demonstrates flouted maxim of relation. Despite these deviations, Arthur's utterances are clearly used with a deliberate communicative purpose, which indicates that while he doesn't strictly adhere to Grice's conversational maxims, his communication serves a specific intent. Overall, the study concludes that Arthur Morgan's use of flouted conversational maxims was an effective strategy to maintain his cover and navigate social interactions during the mission. His use of indirect communication helps him conceal his identity as an undercover member of the gang. This research shows the usefulness of Grice’s conversational maxims in analyzing scripted fictional dialogue and highlights the value of pragmatic analysis in understanding how characters use language strategically in video games.
Reupload file repositori 6 Feb 2026_Maya
Keywords: Flouted Maxims